Recovering 3D color and motion information from multi-view 2D images - Pham, Xuan Hoa. (2010)
Recovering 3D color and motion information of human is a fundamental problem in many applications, including realistic character animation for games and movies, motion analysis for medical diagnostics and sport scene, reconstruction of human appearance and motion for 3D virtual reality. The first step of solving this problem is to recover human information from a sequence of 2D images captured by cameras from many viewpoints.